An empirical assessment of the "healthy prisoner hypothesis". (August 2015) - Baćak, Valerio; Wildeman, Christopher
Abstract: Lower mortality among inmates, compared to the general population, is typically ascribed to access to health care during incarceration and the low risk of death due to homicide, accidents, and drug overdose. In this study, we test an alternative explanation based on selection of healthy individuals into jails and prisons–"the healthy prisoner hypothesis." According to this hypothesis, inmates have to be healthy to commit crimes and become incarcerated, which explains why they experience lower mortality than comparable segments of the general population. Using ten waves of data from the National Longitudinal Survey of Youth 1997, we compare individuals who become incarcerated the following year to those who do not on four measures of health—depression, self-rated health, functional limitations, and injury or illness requiring medical attention. Results from matched samples indicate that future inmates are hardly ever in significantly better health the year prior to their incarceration. These findings strongly suggest that the paradoxical mortality advantage of inmates is not due to health selection. Highlights: This was a first empirical assessment of the "healthy prisoner hypothesis". Health of future inmates was compared to their non-incarcerated counterparts. Mortality advantage of inmates is unlikely due to positive health selection.